A STUDY ON THE ANTIDEPRESSANT EFFECT OF DANZHI XIAOYAO POWDER - Lun, Zheng (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Danzhi Xiaoyao Powder is used for regulating qi and blood, soothing liver-qi stagnation and adjusting the function of internal organs in the clinical. The objective of this paper was to study the antidepressant effect of Danzhi Xiaoyao Powder. Methods: Experimental animals were grouped and given different doses of xiaoyao powder and Fluoxetine Hydrochloride tablets respectively. Mouse models of behavioural despair such as tail suspension test and forced swimming test were used to evaluate the antidepressant effect of Xiaoyao. Results: Danzhi Xiaoyao Powder could shorten the immobility time of mice in the tail suspension and forced swimming despair models, and had a significant effect on them, while having no significant effect on locomotor activity in mice. Conclusion: Danzhi Xiaoyao Powder has a good antidepressant effect. The material basis and physiological and biochemical mechanisms of its action should be determined by further study.